2023
DOI: 10.1002/smll.202205744
|View full text |Cite
|
Sign up to set email alerts
|

A Spiky Silver‐Iron Oxide Nanoparticle for Highly Efficient Targeted Photothermal Therapy and Multimodal Imaging of Thrombosis

Abstract: Thrombosis and its complications are responsible for 30% of annual deaths. Limitations of methods for diagnosing and treating thrombosis highlight the need for improvements. Agents that provide simultaneous diagnostic and therapeutic activities (theranostics) are paramount for an accurate diagnosis and rapid treatment. In this study, silver‐iron oxide nanoparticles (AgIONPs) are developed for highly efficient targeted photothermal therapy and imaging of thrombosis. Small iron oxide nanoparticles are employed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 79 publications
1
13
0
Order By: Relevance
“…The iron oxide core also functioned as a surface template for the silver ion coating and acted as a donor of electrons for the growth of the Ag layer. The silver coating was formed via a seeding technique, whereby reducing agents were employed to reduce the salts in the silver nitrate solution . Here, the seedings of silver nucleation were developed by the utilization of sodium citrate, hydroxylamine, and the citrate-coated iron oxide nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The iron oxide core also functioned as a surface template for the silver ion coating and acted as a donor of electrons for the growth of the Ag layer. The silver coating was formed via a seeding technique, whereby reducing agents were employed to reduce the salts in the silver nitrate solution . Here, the seedings of silver nucleation were developed by the utilization of sodium citrate, hydroxylamine, and the citrate-coated iron oxide nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the addition of silver nitrate aliquots formed a silver seed on the surface of the IONPs. Previously reported studies from our group have demonstrated that the mass ratio between silver and iron (Ag/Fe) and the amount of hydroxylamine employed are crucial for the asymmetrical spiky shaped NPs and their strong absorbance in the NIR. , The optimized protocol involves the utilization of 20 μL of 50% hydroxylamine and a 1.18 mass ratio of Ag/Fe in the reaction. It should be noted that preliminary imaging studies of NPs were performed to ascertain both MRI and PAI contrast abilities to confirm parameters such as the Ag/Fe ratios in the synthesis reaction as these NPs were developed to be effective in both photothermal treatment strategy and dual-imaging ability using MRI and PAI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two types of hyperthermia depending on the stimulus used as a trigger, i.e ., optical or magnetic properties activated nanoheating agents. Magnetic hyperthermia (MHT) utilizes heat dissipation by MNPs to kill tumor cells when under an alternating magnetic field (AMF), while photothermal therapy (PTT) employs photothermal agents that are activated by near-infrared laser (NIR) irradiation. However, both magnetic hyperthermia and photothermal therapy have their limitations. , For instance, highly concentrated intratumoral injections of magnetic nanoparticles are required to compensate the low specific loss power (SLP) under low magnetic field intensity for the MHT, the real-time temperature monitoring is invasive thermometry, and the nanoparticles distribute non-uniformly within the tumor . Therefore, enhancing SLP value through modifications in the material properties, size, shape, and aggregation state of magnetic nanoparticles emerges as the pivotal factor for augmenting the effectiveness of magnetic hyperthermia. In PTT, high-power laser exposure can damage surrounding healthy tissue, and some nanoparticles (gold and silver) used are not FDA-approved materials and may not meet biosafety requirements .…”
Section: Introductionmentioning
confidence: 99%